Identifying important and feasible primary care structures and processes in the US healthcare system: a modified Delphi study - Daphna Harel; Bryan J Weiner; Saul B Blecker; Ann M Nguyen; Maggie M Paul; Stephanie L Albert; Lorraine Kwok; Donna R Shelley; Charles M Cleland; Deborah J Cohen; Laura Damschroder; Carolyn A Berry (BMJ Open)
Objective To identify primary care structures and processes that have the highest and lowest impact on chronic disease management and screening and prevention outcomes as well as to assess the feasibility of implementing these structures and processes into practice.Design A two-round Delphi study was conducted to establish consensus on the impact and feasibility of 258 primary care structures and processes.Participants 29 primary care providers, health system leaders and health services researchers in the USA.Outcomes Primary outcomes were (1) consensus on the impact of each structure and process on chronic disease management and screening and prevention outcomes, separately and (2) consensus on feasibility of implementation by primary care practices.Results Consensus on high impact and feasibility of implementation was reached on four items for chronic disease management: ‘Providers use motivational interviewing to help patients set goals’, ‘Practice has designated staff to manage patient panel’, ‘Practice has onsite providers or staff that speak the most dominant, non-English language spoken by patients’ and ‘Practice includes mental health providers and/or behavioural health specialists in care team’ and seven items for screening and prevention: ‘Practice utilizes standing protocols and orders’, ‘Practice generates reports to alert clinicians to missed targets and to identify gaps in care, such as overdue visits, needed vaccinations, screenings or other preventive services’, ‘Practice has designated staff to manage patient panel’, ‘Practice sets performance goals and uses benchmarking to track quality of care’, ‘Practice uses performance feedback to identify practice-specific areas of improvement’, ‘Practice builds quality improvement activities into practice operations’ and ‘Pre-visit planning data are reviewed during daily huddles’. Only ‘Practice has designated staff to manage patient panel’ appeared on both lists.Conclusion Findings suggest that practices need to focus on implementing mostly distinct, rather than common, structures and processes to optimise chronic disease and preventive care.